Genotoxicity of radiofrequency electromagnetic fields: Protocol for a systematic review of in vitro studies. (March 2021) - Romeo, Stefania; Zeni, Olga; Sannino, Anna; Lagorio, Susanna; Biffoni, Mauro; Scarfì, Maria Rosaria
Abstract: Background: Exposure to radiofrequency electromagnetic fields (RF-EMF, 100 kHz – 300 GHz) emitted by wireless communication technologies is pervasive and ubiquitous. Concern has been raised about possible adverse effects to human health. In 2011 the International Agency for Research on Cancer has classified RF-EMF as possibly carcinogenic to humans, highlighting that the evidence is weak and far from conclusive. Updated systematic reviews of the scientific literature on this topic are lacking, especially for mechanistic studies. Objectives: To develop a protocol for a systematic review of experimental studies investigating genotoxic effects induced by RF-EMF in in vitro cellular models. Genotoxicity is one of the key-biological indicators of carcinogenicity, and the most common characteristics of established carcinogens. The predefined procedures for conducting the systematic review are outlined below. Methods: We will follow the guidelines developed by the National Toxicology Program-Office of Health Assessment and Translation (NTP-OHAT), adapted to the evaluation of in vitro studies. Eligibility criteria: We will include experimental in vitro studies addressing the relationship between controlled exposures to RF-EMF and genotoxicity in mammalian cells only. Eligibility for inclusion will be further restricted to peer reviewed articles reporting findings from primary studies. Information sources: We will search the scientific literature databases NCBI PubMed, Web of Science, and EMF-Portal. No filter on publication date will be applied. Only studies published in English will be considered. The reference lists of the included papers and available reviews will be screened for unidentified relevant papers. References will be managed through Endnote X9 software. Data extraction and synthesis of results: Data from included papers will be extracted according to predefined forms. Heterogeneity within the available evidence will determine the type of evidence synthesis that is appropriate. Findings will be summarized in tables, graphical displays and in a narrative synthesis of the available evidences. A meta -analysis will be carried out if subgroups of studies homogeneous in terms of exposure characteristics, endpoint, and cell types will be identified. Risk of bias: The internal validity of included studies will be assessed using the NTP-OHAT Risk of Bias Rating Tool for animal studies, adapted to in vitro studies. This stage of the process will be managed through the Health Assessment Workspace Collaborative (HAWC). Evidence appraisal: To rate confidence in the body of evidence, we will use the OHAT GRADE-based approach for animal studies. Framework and funding: This protocol concerns one of the evidence streams considered in a larger systematic review of the scientific literature on the potential carcinogenicity of RF-EMF, performed by scientists from several Italian public research agencies. The project is supported by the Italian Workers' Compensation Authority (INAIL) in the framework of the CRA with the Istituto Superiore di Sanità "BRiC 2018/06 – Scientific evidence on the carcinogenicity of radiofrequency electromagnetic fields".